First Breeding Record of Red-wattled Lapwing Vanellus indicus (Charadriiformes: Charadriidae) in Indonesia - Abdul Hakim Syah; Yuli Seperi; Muhammad Iqbal (BIO PALEMBANICA, 2026)
Indonesia contains extensive tropical wetland ecosystems that provide important habitats for resident and migratory waterbirds within the East Asian Australasian Flyway. However, breeding documentation for several shorebird species in the Indonesian archipelago remains limited. Here we document the first confirmed breeding record of Vanellus indicus in Indonesia based on field observations conducted on 18 January 2026 in Pinang Kencana Subdistrict, Tanjungpinang Timur District, Bintan Island, Riau Islands Province. Evidence of breeding was established through the observation of a downy chick accompanied by adult birds exhibiting territorial defense and distraction behavior. A follow up visit on 21 February 2026 confirmed the presence of adult birds and a juvenile, indicating successful breeding at the site. This record expands current knowledge of the species’ distribution and breeding status, and suggests that Indonesian lowland wetlands may support newly established breeding populations of adaptable shorebird species.